1 Putting research into practice: knowledge translation and implementation for action on nutrition. (12th April 2022) - Bell, Jack; Fallows, Ellen; Dael, Peter Van; McAuliffe, Shane; Kohlmeier, Martin; Hernandez, Alfredo Martinez; Adamski, Melissa; Ray, Sumantra; Crocombe, Dominic; Vale, Marjorie Lima do
Abstract : The transfer of research evidence into practice has been historically slow, and requires an integration of many elements, including quality evidence, supportive physical and intellectual environments, and facilitation, as discussed at the NNEdPro Sixth International Summit on Nutrition and Health. Examples of applying clinical research into practice focused on the use of group consultations (also known as group clinics or shared medical appointments) to support behaviour change, the role of dietary micronutrients during the COVID-19 pandemic and the potential of Precision Nutrition. An emerging area from early implementation evidence includes group consultations, also known as shared medical appointments, as discussed by Dr Fallows. Group consultations have been shown to improve clinical outcomes for some patient groups (e.g., HbA1c, lipids, BMI), as well as improve self-care and health education, and patient and clinician satisfaction. These groups have been piloted throughout the UK both face-to-face and virtually, with initial findings suggesting they are feasible and acceptable to patients and clinicians. Further work is needed to assess whether these could be cost-effective when scaled-up in National Health Service UK primary care. During the COVID-19 pandemic, there has been increasing emphasis on the central role of nutrition in health, including the role of dietary micronutrients, as discussed by Dr Van Dael and Shane McAuliffe. Nutrition plays an important role in immunity, yet the nutritional status of the most vulnerable population groups is likely to deteriorate further due to the health and socio-economic impacts of the novel coronavirus. Thus, implementation of this evidence into health care practice is key. Precision Nutrition, defined as an 'approach that uses information on individual characteristics to develop targeted nutrition advice, products or services', offers an exciting opportunity to further individualise dietary advice for behaviour change, as discussed by Dr Kohlmeier and Dr Hernandez. Precision nutrition is underpinned by the recognition that individuals differ in many important ways due to identifiable molecular traits and can be utilised to determine personalised weight loss interventions based on genetic variants. Use of implementation science is in line with one of the six cross-cutting pillars of the Nutrition Decade: Aligned health systems for universal coverage of nutrition actions. Dr Bell, an Advanced Accredited Practising Dietitian in Australia, provided an overview of key implementation science models and frameworks. Implementation frameworks such as the Action Research Framework, the Knowledge to Action Cycle, and the Spread and Sustain Framework, are underpinned by knowledge creation, effective education, and culture change. Dr Bell then highlighted how theoretical frameworks have provided guidance for the implementation of real world, complex nutrition interventions, including the Systematised Interdisciplinary Program for Implementation and Evaluation (SIMPLE) in Australia, and the More-2-Eat program in Canada.